The role of multimedia in enhancing achievement motivation in mathematics: a case study on the seventh grade students in North Eastern province, Sultanate of Oman - دور الوسائط المتعددة في تعزيز دافية الإنجاز في الرياضيات: دراسة حالة على طلاب انصف السابع في مقاطعة شمال الشرقية بسلطنة عمان - Humaid Al Jabri, Isehaq Humaid Said; Sahrir, Muhammad Sabri (OCERINT International Organization Center of Academic Research, 2020)
This quantitative, analytical study discusses the impact of multimedia on enhancing motivation among seventh graders in the Northeastern District. Where the problem arose in the fact that research and studies indicated the low level of performance of seventh-graders in the mathematics lesson, and that the teaching method used is dominated by speech and instruction by the teachers, memorization by the students, without improving the level of his higher thinking capabilities and motivations in studying Maths. Therefore, the study aims to discuss the effect of multimedia on enhancing motivation among seventh-graders, and to know the statistically significant differences at the level of significance (0.05) between the mean scores of the pre and post measurements of students of the experimental group that studied according to the multimedia program on the motivation scale for achievement in mathematics. Find out the teachers’ suggestions on developing the multimedia program. The researcher used the descriptive approach and the semi-experimental approach to a sample of (153) mathematics students, that was divided into a control group (77) students, and an experimental group (76) students. The study tools included; the achievement test in the skills of solving the pre and post mathematical problems of the control and experimental group, the motivation scale in mathematics consisting of (33) paragraphs. The findings revealed that the multimedia program affects improving achievement motivation among students by (13.1%) of achievement level for the experimental group, and that there are statistically significant differences at the significance level (0.05) between the average achievement of the experimental group students, and the average achievement of the control group students in The level of motivation for achievement in mathematics subject, and the differences were in favor of the experimental group students sample